Analisis Pengaruh Rasio Keuangan Terhadap Return Saham Pada Perusahaan Otomotif Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2009-2013 - Novalia, Dewandani Erien, Imron Rosyadi, S.E., M.Si (2015)
The purpose of this study is to analyze the influence of ROA, DER and EPS partially on stock returns and analyze the influence of ROA, DER, and EPS significantly on stock returns. This study uses secondary data. The sample in this study as many as 13 automotive companies listed in the Indonesia Stock Exchange on the period 2009 to 2013 provided by ICDM. The sampling technique using purposive sampling techniques or sampling based on the considerations and specific criteria. The analytical method used is multiple linear regression analysis with the first test classic assumptions which include normality test, multicollinearity, heteroscedasticity test and autocorrelation test. With hypothesis testing using simultaneous significant (F test) and partial significance test (t-test) and the coefficient of determination (R ²) with ofestimate used standard error of 5% or 0.05. ROA does not have a significant impact on Stock Return. DER variables have a significant influence on Stock Return. Variable EPS does not have a significant impact on Stock Return. F test analysis results of ROA, DER, and EPS jointly significant to Return Saham. So model used is fit and the calculation results for the R2 value obtained in the multiple regression analysis coefficient obtained figures with adjusted-R2 of 0.035. This means that 35% Stock Return variable variation can be explained by the variable ROA, DER, and EPS while the remaining 65% is explained by other factors outside the model studied.